The English - Mustika, Made Dwi Setyadhi; Yuliarmi, Ni Nyoman (Jurnal Ekonomi Kuantitatif Terapan, 2024)
During this time, the main reason someone migrates is related to the motivation to get a better job . However, the other reason that can not be ignored is the expectation to get the opportunity of having a higher level of education . A phenomenon that occurs following the educational migration is many educational migrants did not return to their origins after finishing their studies, and would choose to work in the destinations . This phenomenon is known as brain drain, which refers to the condition where the educational migrants did not return to their origins after fisnishing their studies in the destinations . This study covers educational migration activities between regions in Indonesia, so the term used to describe this condition is the domestic brain drain. This study aimed to analyze the determinant of the brain drain phenomenon in educational migration activities. By using panel data of the Indonesian Family Life Survey (IFLS) wave 5, which were processed using the Logistic Regression Model method, the result suggested that about 49.08 percent of educational migrants in Indonesia chose not to return to their origins after finishing their studies. They decided to work in the destination or in other areas outside the area of their origins. Their decisions were significantly affected by the amount of salary/income, marital status, location of parents' residence, health facilities, sex, age, age square, province of the origin, and geographical. Partially, marital status, the residence of the parents, age square, and geographical, have a negative impact to migrant’s decision. Meanwhile, health facilities, sex, and age have a positive impact to migrant’s decision.